2014
DOI: 10.1158/1055-9965.epi-14-0724
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Black and White Participants in the Selenium and Vitamin E Cancer Prevention Trial (SWOG-Coordinated Intergroup Study S0000)

Abstract: Background Disproportionally low retention of minority populations can adversely affect the generalizability of clinical research trials. We determine the overall retention rates for White and Black participants from the Selenium and Vitamin E Cancer Prevention Trial (SELECT) and explore participant and site characteristics associated with retention failure (study disengagement)for these groups. Methods A secondary analysis of 28,118 White (age ≥55), and 4,322 Black (age ≥ 50) SELECT participants used multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…One study showed that Black Americans' disengagement from clinical trials is twice that of Whites. 19…”
Section: Barriers For Black Americans Participation In Cancer Clinica...mentioning
confidence: 99%
“…One study showed that Black Americans' disengagement from clinical trials is twice that of Whites. 19…”
Section: Barriers For Black Americans Participation In Cancer Clinica...mentioning
confidence: 99%
“…Similarly, lower rates exist for those patients who transition from pediatric to adolescent and youngadult cancers. Many issues, such as prevailing sociodemographics, trust issues, comorbidity burdens, and competing priorities, contribute to the situation (50). However, community engagement is vital to address the fundamental recruitment and retention challenges that cloud the clinical trials setting.…”
Section: Current Issues/state Of Knowledgementioning
confidence: 99%
“…Similarly, lower rates exist for those patients who transition from pediatric to adolescent and young adult cancers. Many issues, such as prevailing sociodemographics, trust issues, comorbidity burdens, and competing priorities, contribute to the situation . However, community engagement is vital to address the fundamental recruitment and retention challenges that cloud the clinical trials setting.…”
Section: Redesigning Clinical Trials To Acknowledge and Address Cancementioning
confidence: 99%